2021
DOI: 10.1155/2021/5571862
|View full text |Cite|
|
Sign up to set email alerts
|

Augmented Reality Research of Measuring X-Ray Dental Film Alveolar Bone Based on Computer Image Analysis System

Abstract: The important application of computer imaging technology in the medical field is a necessary auxiliary method for clinical diagnosis and treatment. At present, many people are affected by various factors and have various problems caused by the dental cellular bone. Traditional treatment methods are complex and long, which can cause damage to body tissues. Based on this problem, this paper takes the augmented reality measurement of X-ray dental film as the research object. Based on the in-depth measurement algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The main development objective of smart medicine is the application of technology and operation. In the current medical environment, how to better understand and transform user expectations and needs and how to use virtual reality technology to better integrate product structure and functions with user needs are key issues in clinical medicine [ 19 , 20 ]. The key points of the application conform to the following formula: …”
Section: Preoperative Auxiliary Methods For Solitary Nodules In the Lungmentioning
confidence: 99%
“…The main development objective of smart medicine is the application of technology and operation. In the current medical environment, how to better understand and transform user expectations and needs and how to use virtual reality technology to better integrate product structure and functions with user needs are key issues in clinical medicine [ 19 , 20 ]. The key points of the application conform to the following formula: …”
Section: Preoperative Auxiliary Methods For Solitary Nodules In the Lungmentioning
confidence: 99%
“…Our study thus combined panoramic and periapical film to build a prediction model. Alveolar bone structure assessment and tooth segmentation in panoramic film are most studied in literature (24)(25)(26). U-net or mask R-CNNs are often used as the backbone for different segmentation models for panoramic radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%